Writing history in the present: The implications of localized forms of science in Latin America for a postcolonial world (Alternautas, 2022)
Scientific research practices, in particular in the biological sciences, are currently undergoing a great deal of scrutiny and change due to recent debates in the social sciences about bioprospecting, biopiracy and the co-production of knowledge. Nowhere are these debates more relevant than in countries with high levels of both biological and cultural diversity that have been subject to a history of colonialism, such as in tropical regions of South America. Many authors have written critically about these issues – however, there is less understanding about the links between such histories and the policies, discourses and relationships as occur in scientific practices in these regions of the world today. In particular, little notice has been taken of localized creations of scientific practice in non-western settings, especially in terms of how they shift scientific trends and debates on a global scale. This essay takes the case of ‘Bolivian science’ in order to show how research encounters in the so-called scientific ‘peripheries’ of the world can have implications for the production and use of science that far outstretch the limits of geographical boundaries, and lead to the decolonization of science back on Western soils.